The Relationship Between Mothers' Knowledge And Husbands' Support With The Success Of Exclusive Breastfeeding In The Working Area Of The Kandang Community Health Center In Bengkulu City In 2025 - Afrrilia, Wiwin; Putri, Yesi; Umami, Desi Aulia (CV. Utami, 2026)
Exclusive breastfeeding refers to providing only breast milk and no other food or drink to infants from birth to 6 months of age, except for medications and vitamins (Humune et al., 2020). A 2022 survey by the World Health Organization (WHO) found that exclusive breastfeeding coverage in Indonesia was 67.96%, compared to 69.7% in 2021. This data indicates a decline in exclusive breastfeeding coverage (WHO, 2023). Data from Bengkulu Province recorded exclusive breastfeeding coverage of 66.5% in Bengkulu City (Health Profile of Bengkulu Province). This study aims to determine the correlation between maternal knowledge and husband's support and the success of exclusive breastfeeding in the Working Area of Kandang Health Center of Bengkulu City. The method used was an analytical research design with a cross-sectional approach. Data were collected by distributing questionnaires to 43 respondents using a total sampling technique. Univariate analysis results showed that almost half of the respondents (46.5%) had insufficient knowledge, the majority (58.1%) did not receive support from their husbands, and the majority (55.8%) did not provide exclusive breastfeeding. Bivariate analysis results showed a significant correlation between maternal knowledge and husband's support and the success of exclusive breastfeeding in the Working Area of Kandang Health Center of Bengkulu City (p-value = 0.01). It is recommended that the health center provide education on exclusive breastfeeding and the factors influencing its success.